THE DEVELOPMENT OF PACKAGING DESIGN OF MORINGA TEA BAG AND MORINGA POWDER PRODUCTION OF KWT SRI REJEKI - Karina Citra Rani; Nikmatul Ikhrom Eka Jayani; Noviaty Kresna Darmasetiawan; Elsye Tandelilin; Prayogo Widyastoto Waluyo (Universitas Muhammadiyah Mataram, 2021)
Abstrak: Kelompok Wanita Tani (KWT) Sri Rejeki Desa Bogo merupakan kelompok yang dibentuk oleh Bumdes Desa Bogo dalam bidang produksi berbagai macam produk berbasis kelor, antara lain teh dan serbuk kelor. Kualitas dan desain kemasan kedua produk yang selama ini digunakan masih terbatas dari segi stabilitas dan belum memberikan ciri khas produk. Tujuan dari pelaksanaan program pengembangan desain kemasan ini adalah untuk melakukan perbaikan kemasan kedua produk melalui pemilihan bahan kemas yang optimal, pemilihan komposisi warna yang meningkatkan atensi konsumen, penambahan logo ciri khas produk dan informasi produk. Metode pelaksanaan kegiatan dilakukan melalui pelatihan konsep desain kemasan, pendampingan penyusunan prototipe kemasan, dan aplikasi kemasan baru pada produk. Pelaksanaan kegiatan melibatkan KWT Sri Rejeki, tim PPDM Sentra Kelor, Bumdes Langgeng Makmur, dan Pemerintah Desa Bogo. Hasil program ini adalah kemasan baru untuk produk teh dan serbuk daun kelor dengan kualitas yang lebih baik, desain yang lebih menarik, dan terdapat informasi serta ciri khas produk. Penjualan produk mengalami peningkatan dan kepercayaan konsumen terhadap kualitas produk meningkat setelah digunakan kemasan baru luaran program ini. Abstract: Sri Rejeki Farming Women Group of Bogo village (KWT) is a group formed by Bumdes Desa Bogo in the production of various types of moringa-based products, including tea and moringa powder. The quality and packaging design of the two products which was previously used are still limited in terms of stability and do not yet provide product characteristics. The aim of implementing this packaging design development program is to renew the packaging of the two products by selecting optimal packaging materials, adjusting color compositions that increase consumer preferences, implementing product characteristic logos and product information. The method of implementing these activities is carried out through training on packaging design concepts, assistance in the preparation of packaging prototypes, and application of new packaging to the products. The implementation of this activity involved KWT Sri Rejeki, PPDM Sentra Kelor team, Bumdes Langgeng Makmur, and the Bogo Village Government. The result of this program is the new packaging for tea products and Moringa leaf powder with better quality, more attractive design, additional product information and, product characteristics. Product sales have increased and consumer confidence in product quality has increased after the use of new packaging resulted from this program.